Reconstruction of mean January air temperature of Holocene in the lower Kolyma River region - N. A. Budantseva; Yu. K. Vasil’chuk (Лëд и снег)
The object of study is ice wedges at 10 sites in the lower Kolyma River. The Holocene age of ice wedges is determined on the basis of radiocarbon dating of the enclosing sediments and location of ice wedges in alases, ﬂoodplains and lacustrine-paludal basins. The analysis of radiocarbon dates has shown that formation of alases with ice wedges began in early Greenlandian stage of Holocene (the oldest dates are 11 and 10.8 cal ka BP). The most active alas development and syngenetic ice wedge growth occurred since the second half of the Greenlandian stage till the middle-late Northgrippian stage of the Holocene, most of the available 14C dates fall in the range from 9.5 to 4.2 cal ka BP. Accumulation of the ﬂoodplain deposits of the Kolyma River occurred mainly during the Meghalayan stage, according to obtained 14C dates from 2.5 to 1.9 cal ka BP. Oxygen isotope data of studied ice wedges show that for the Holocene ice wedges the range of δ18O is about 4 ‰ (from –28 to –23.7 ‰) and for the modern ice veinlets– about 5 ‰ (from –28.1 to –23 ‰). Water of meteoric origin was the main source for ice wedge formation, however, for ice wedges on the ﬂoodplains some participation of surface (river) water is not excluded. Based on the reﬁned equation of the ratio between ice wedge isotope composition and mean January air temperature, paleotemperatures for three key periods of the Holocene were calculated. It was established that mean January air temperature during the Holocene varied in the approximately same range: from –40.7 to –33.8 °С during the Greenlandian stage, from –38.6 to –33.3 °С during the Northgrippian stage and from –41.5 to –33 °С during the Meghalayan stage. This most likely indicates the stability of winter climatic conditions in the north of Yakutia during the Holocene, determined by the inﬂuence of Siberian anticyclone.